A system for the documentation and validation of non-formal and informal learning of engineers (NFIF) - Alfredo Soeiro (2017)
The main goal of the entire project was the creation in several phases of an overall concept, i.e. a sys-tem, for the documentation and validation of non-formal and informal learning activities. This initial development phase was followed by a implementation phase. This meant the integration of the con-cept into the already existing database system of the engineering card of VDI by creating a prototype application for testing and marketing purposes. The entire process included the revision of VDIs engi-neering card database as well as the creation of a blueprint for a handbook and several working docu-ments.During the course of the project, dissemination by FEANI and the project partners of the project goals and achievements to as many engineering organizations and other stakeholders as possible played a major part. This included information and consultation processes with different stakeholder groups on the European as well as the national level. However, dissemination was rather difficult and only three of the originally planned multiplier events were realized during the final phase of the project. Thus, some stakeholders were integrated into the project. From the view of the project partners, this has lead to an increased publicity and broader acceptance of the project in particular and the engineering card in general.In the long run, the wide dissemination of the engineering card as the only professional card exclu-sively for engineers will hopefully lead to growing transparency on the European labor market for en-gineers. This would benefit the European economy in two ways. On one hand, it would be highly ben-eficial for companies looking for qualified labor, thus helping to reduce the lack of qualified personnel in some countries. On the other hand, in countries with a large surplus of highly qualified personnel, professional mobility will increase with the availability of an instrument simplifying the often very complex and time-consuming recognition processes.For European political decision makers the engineering card offers a prototype for a simple, non-bu-reaucratic and well-tested system for recognition of professional qualifications and training. The engi-neering card may therefore function as a blueprint for projects with similar goals.